Students’ learning skills, learning modes and their mental types : Its linkage to academic achievements of university students / Za’faran Hassan - Hassan, Za’faran (Universiti Teknologi MARA Cawangan Pahang, 2005)
Today’s competitive world where academic achievement is important to secure at least a decent job means that most students in universities are struggling to succeed in their pursuit of paper qualifications that may assist them in embarking on their career path. What then are the factors contributing to academic excellence of students in universities? Nevertheless, the question if academic excellence and achievement is of crucial relevance because only those who excel in their academic achievements can survive and ultimately succeed in obtaining their degrees in their respective areas of study. This study sought to enhance understanding of factors influencing academic achievement of Malaysian university students.. The study was conducted utilizing a sample of students attending the ‘Academic Enhancement Program’ (AEP) organized by the Student Affairs Unit of University Technology MARA, Malaysia The results of the study poses some interesting findings relating to students learning attitude, the study skills that they perceived they possess, their modes of study and the students mental types.